Hollow porous adsorption material as well as preparation method and application thereof

By growing covalent organic frames on the surface of metal organic frames and etching metal organic frames, hollow porous adsorption materials are prepared, which solves the problem of low adsorption efficiency of target pollutants in food, and achieves efficient adsorption and enrichment and improves the stability of the material.

CN119425635APending Publication Date: 2025-02-14NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310975093.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing covalent organic framework materials have low adsorption efficiency of target pollutants in food and are difficult to play an internal pore, which limits their application in food safety testing.

Method used

The covalent organic frame is grown on the surface of the metal organic frame by in situ growth method to form a core-shell structure composite material, and the metal organic frame is etched by acid to prepare a hollow porous adsorption material.

Benefits of technology

Efficient adsorption and enrichment of target pollutants is achieved, and the hollow structure of the material increases the adsorption speed and quantity, while having higher chemical stability and thermal stability, suitable for sample pretreatment of complex substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425635A_ABST
    Figure CN119425635A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow porous adsorption material and a preparation method and application thereof.A covalent organic framework successfully grows on the surface of a metal organic framework through an in-situ growth method to form a core-shell structure composite material, and then the metal organic framework is etched with acid to prepare the hollow porous adsorption material. The prepared hollow porous adsorption material has good particle size uniformity and has remarkable and efficient adsorption capacity on target pollutants, the adsorption speed and the adsorption capacity are greatly improved due to the hollow structure of the material, and the hollow porous adsorption material can be used for enriching pollutants in food; the hollow porous adsorption material has higher chemical stability and thermal stability, stably exists in various organic solvents, and is suitable for sample pretreatment of complex matrixes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a hollow porous adsorption material and a preparation method and application thereof. Background Art

[0002] Risk factors for food safety From farmland to dining table, there may be factors that affect food safety at every stage, such as microbial hazards, heavy metal pollution, pesticide and veterinary drug residues, excessive additives, hazards in the processing, storage and packaging process, persistent organic pollutants, biological toxins and food adulteration, etc., which pose a great threat to the life and health of consumers. The importance of food testing for food safety should be implemented in specific industry norms and standards, so as to avoid food safety problems, fully protect people's health, and the food industry can achieve sustainable development and progress. Food testing technology is constantly developing, and traditional testing methods can no longer meet the safety testing needs of modern food, and food matrices are often more complex. Therefore, more efficient and convenient testing methods are urgently needed to better control food safety issues and promote the food industry to develop in a green and safe direction.

[0003] Covalent organic frameworks are porous crystalline polymers composed of light elements such as carbon, boron, oxygen and silicon connected by strong covalent bonds in 2D or 3D topology. In COF, the secondary building units are firmly held by strong covalent bonds between carbon-nitrogen, boron-oxygen, silicon-carbon or boron-oxygen-silicon, so they have strong chemical stability. Since it can be designed into a target framework structure or functional group for the bonding of target pollutants, it can achieve efficient adsorption of target hazards and become a hot topic in the field of detection. The prepared covalent organic framework has high-intensity pores, but its contribution mainly comes from the pores distributed on the surface of the covalent organic framework. Most of the internal pores cannot play a role due to inaccessibility, which greatly limits its application in actual samples. Developing new hollow porous adsorption materials, reducing the transmission distance from the target to the material, improving the adsorption efficiency of the material for the target pollutant, and ultimately achieving the enrichment and detection of food hazards, provides a technical basis and important social value for the efficient detection, effective supervision and control of hazards in food. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a hollow porous adsorption material and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is: a method for preparing a hollow porous adsorption material, in which a covalent organic framework is successfully grown on the surface of a metal organic framework by an in-situ growth method to form a core-shell structure composite material, and then the metal organic framework is etched by acid to prepare a hollow porous adsorption material.

[0006] Preferably, the specific steps are as follows:

[0007] Step 1: Dissolve Zn(NO3)2·6H2O and dimethylimidazole in 25 mL of methanol at a ratio of 1:4. The resulting methanol solution of Zn(NO3)2 is marked as solution A, and the methanol solution of dimethylimidazole is marked as solution B. Add solution B to solution A and stir to react. Collect and dry the generated solid to obtain ZIF-8.

[0008] Step 2: Disperse and dissolve 0.08 mM 1,3,5-tri(4-aminophenyl)benzene and 0.12 mM terephthalaldehyde in 25 mL methanol, add 8 mg ZIF-8, and then add lead chloride solution, mix thoroughly; after standing at room temperature, collect and dry the solid matter to obtain ZIF-8@COF;

[0009] Step 3: Add 20 mg ZIF-8@COF to 10 mL 1M HAc for etching. Collect and dry the obtained solid material to obtain the hollow porous adsorption material HCOF.

[0010] Preferably, in step 1, the molar ratio of Zn(NO3)2·6H2O to dimethylimidazole is 1:4.

[0011] Preferably, in step 2, 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde are dispersed and dissolved in methanol and ultrasonically treated until completely dissolved; after adding ZIF-8 and lead chloride solution, shake vigorously for 10 seconds and then stand at room temperature for 24 hours.

[0012] Preferably, the concentration of the lead chloride solution is 0.1 mol / L.

[0013] Preferably, the concentration of acetic acid in step three is 1M.

[0014] The hollow porous adsorption material is prepared by the method for preparing the hollow porous adsorption material.

[0015] Application of hollow porous adsorbent materials in enrichment of pollutants in food.

[0016] Preferably, the hollow porous adsorption material is placed in the target solution, and the food contaminants are enriched by vibration adsorption.

[0017] Preferably, the hollow porous adsorption material after enrichment of pollutants can be eluted with acetonitrile to remove pollutants and then reused to enrich food pollutants.

[0018] The advantages and positive effects of the present invention are: the prepared hollow porous adsorption material has good particle size uniformity, has significant and efficient adsorption capacity for target pollutants, and the hollow structure of the material greatly improves the adsorption speed and adsorption amount. At the same time, the hollow porous adsorption material has higher chemical stability and thermal stability, exists stably in a variety of organic solvents, is suitable for sample pretreatment of complex matrices, and can achieve efficient adsorption, enrichment and removal of hazardous substances. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Transmission electron microscopy images: (a) metal organic framework; (b) covalent organic framework; (c) composite porous adsorption material; (d) hollow porous adsorption material; scanning electron microscopy images: (e) metal organic framework; (f) covalent organic framework;

[0020] Figure 2 (a) Fourier transform infrared spectrum of hollow porous adsorption material; (b) XRD pattern; (c) N2 adsorption-desorption isotherm and pore size distribution; (d) thermogravimetric analysis curve;

[0021] Figure 3 Stability test of hollow porous adsorption materials: (a) Fourier transform infrared spectra after 24 h of treatment with different solvents; (b) Fourier transform infrared spectra after 48 h; (c) XRD spectra after 24 h of treatment with different solvents; (b) XRD spectra after 48 h;

[0022] Figure 4 Hollow porous adsorption materials: (a) Study on the adsorption kinetics of Aspergillus flavus; (b) Study on the adsorption equilibrium of Aspergillus flavus;

[0023] Figure 5 Hollow porous adsorption materials: (a) Study on the adsorption kinetics of advanced glycation end products; (b) Study on the adsorption equilibrium of advanced glycation end products;

[0024] Figure 6 Evaluation of the reusability of hollow porous adsorbent materials. DETAILED DESCRIPTION

[0025] The embodiments of the present invention are described below with reference to the accompanying drawings.

[0026] The present invention relates to a hollow porous adsorption material and a preparation method and application thereof. The hollow porous adsorption material has a typical hollow structure. A simple in-situ growth method is adopted to successfully grow a covalent organic framework on the surface of a metal organic framework to form a core-shell structure composite material. Then, the metal organic framework sensitive to acid is etched by acid through a sacrificial template method to introduce the hollow structure into the covalent organic framework material. Combined with analytical methods such as high performance liquid chromatography and liquid chromatography-mass spectrometry, target pollutants in complex matrix samples are enriched and detected. The prepared hollow porous adsorption material has good particle size uniformity, has a significant and efficient adsorption capacity for target pollutants, and the hollow structure of the material greatly improves the adsorption speed and adsorption amount. At the same time, the hollow porous adsorption material has higher chemical stability and thermal stability, exists stably in a variety of organic solvents, and is suitable for sample pretreatment of complex matrices.

[0027] The preparation method of the hollow porous adsorption material is as follows:

[0028] Step 1: Use the in-situ growth method to prepare a new type of composite porous material with a core-shell structure with strong adsorption and large specific surface area; dissolve Zn(NO3)2·6H2O and dimethylimidazole in methanol at a ratio of 1:4 to form a methanol solution of Zn(NO3)2 (marked as A solution) and a methanol solution of dimethylimidazole (marked as B solution); slowly add B solution to A solution under stirring at room temperature, and continue stirring at room temperature; centrifuge the mixed solution at 4000rpm for 5min, wash with methanol, and dry under high vacuum at 60℃ to collect the white powder product, which is ZIF-8;

[0029] Step 2: Disperse and dissolve 0.08 mM 1,3,5-tri(4-aminophenyl)benzene and 0.12 mM terephthalaldehyde in 25 mL methanol, add 8 mg ZIF-8, and then add lead chloride solution, and mix thoroughly; keep the mixture still at room temperature for 24 hours, centrifuge at 10000 rpm for 10 minutes, wash with tetrahydrofuran and ethanol respectively, vacuum dry the solid, and collect the yellow powder product as ZIF-8@COF;

[0030] Step 3: Synthesize hollow porous adsorption material by sacrificial template method; add ZIF-8@COF to HAc etching, wash the yellow precipitate with water, collect it by centrifugation at 10000 rpm for 10 min, and the obtained yellow powder is the hollow porous adsorption material HCOF.

[0031] The metal organic framework material is combined with the covalent organic framework by the above method, and the acid sensitivity of the metal organic framework is utilized to successfully prepare a covalent organic framework with a hollow structure. The prepared hollow porous adsorption material can be used in food safety testing. The hollow structure is introduced into the covalent organic framework with good chemical stability to achieve convenient pretreatment and rapid and efficient enrichment of target pollutants.

[0032] When in use, the material HCOF is placed in the target solution, and the pollutants in the food sample are adsorbed by vibration to achieve the enrichment of the pollutants. After the pollutants enriched on the HCOF are eluted, the recovered HCOF can be reused to enrich the pollutants in the food sample. The high reuse rate of hollow porous adsorption materials is consistent with the current environmental protection concept, and the non-toxicity of hollow porous adsorption materials also provides a new idea for the removal of harmful substances in the human body. It provides technical support for further strict monitoring and control of harmful substances in food, the formulation of limit standards for harmful substances in food, and the promotion of the application of analytical chemistry methodology based on advanced functional materials in food safety and human health science. It has important leading significance.

[0033] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.

[0034] Example 1: Preparation of hollow porous adsorption material HCOF

[0035] Preparation of ZIF-8: 0.742 g Zn(NO3)2·6H2O and 0.820 g dimethylimidazole were dissolved in 25 mL methanol, marked as solution A and solution B. Then, solution B was slowly added to solution A under stirring at room temperature, and stirring was continued at room temperature for 1 h. The mixture was centrifuged at 4000 rpm for 5 min, washed with methanol 3 times, dried at 60 ° C under high vacuum for 8 h, and the white powder product ZIF-8 was collected.

[0036] Preparation of ZIF-8@COF: Disperse 28.12 g of 1,3,5-tri(4-aminophenyl)benzene and 16.10 g of terephthalaldehyde in 25 mL of methanol and then perform ultrasonic treatment until completely dissolved. Then, add 8 mg of ZIF-8 from step (1) to the above solution, add 50 μL of lead chloride solution, and shake vigorously for 10 seconds. Keep the mixture still at room temperature for 24 hours. After centrifugation at 10000 rpm for 10 minutes, wash with tetrahydrofuran and ethanol three times respectively. Finally, vacuum dry the solid and collect the yellow powder product ZIF-8@COF.

[0037] Preparation of HCOF: Take 20 mg ZIF-8@COF, add 10 mL 1 M HAc and etch for 1 min. The yellow precipitate is washed with water 3 times and collected by centrifugation at 10000 rpm for 10 min. The obtained yellow powder is the hollow porous adsorption material HCOF.

[0038] The prepared HCFO and intermediate products were photographed by transmission electron microscopy and scanning electron microscopy. Figure 1 As shown; among them, (a) is a transmission electron microscopy image of a metal organic framework; (b) is a transmission electron microscopy image of a covalent organic framework; (c) is a transmission electron microscopy image of a composite porous adsorption material; (d) is a transmission electron microscopy image of a hollow porous adsorption material HCFO; (e) is a scanning electron microscopy image of a metal organic framework; (f) is a scanning electron microscopy image of a covalent organic framework; through Figure 1 The content shows the state of material changes during the preparation of HCFO. The prepared porous adsorption material has good morphology and uniform particle size, with a size of about 650nm.

[0039] The chemical properties of the hollow porous adsorption material HCFO were then characterized by Fourier transform infrared spectroscopy analysis, XRD analysis, N2 adsorption-desorption experiment, and thermogravimetric analysis. The results are as follows: Figure 2 As shown, it indicates that the prepared porous network adsorption material has good thermal stability and adsorption performance.

[0040] Example 2: HCFO stability test

[0041] The HCOF material obtained in Example 1 was immersed in PBS, hydrochloric acid (0.1 mol / L), sodium hydroxide (0.1 mol / L) and various organic solvents for 24 h and 7 days, and the Fourier transform infrared spectrum and XRD spectrum of the material were tested. The results are as follows Figure 3 As shown, the prepared hollow porous adsorption material has good chemical stability and structural stability.

[0042] Example 3: HCFO adsorption kinetics and adsorption equilibrium studies

[0043] Adsorption kinetics experiment: 5.0 mg of HCOF obtained in Example 1 was added to 20 mL of standard solution and shaken continuously to ensure sufficient contact between HCOF and the target (AFTs concentration 50 mg / L, shaking for 3, 5, 10, 20, 30 min; AGEs concentration 20 mg / L, shaking for 3, 6, 8, 10, 20, 30, 40 min). HCOF was then collected and the supernatant was analyzed by HPLC-MS / MS or HPLC. The adsorption kinetics of covalent organic frameworks were determined by the same method (AFTs concentration 8 mg / L, shaking for 5, 10, 20, 30, 40, 40, 50, 60, 70, 80, 90 min; AGEs concentration 10 mg / L, shaking for 5, 10, 20, 30, 40 min).

[0044] Adsorption equilibrium experiment: 5.0 mg of HCOF obtained in Example 1 was added to 20 mL of standard solution, and then continuously shaken to ensure sufficient contact between HCOF and the target ((AFTs concentration was 10, 20, 30, 45, 45, 50 and 60 mg / L, shaking for 10 min; AGEs concentration was: 5, 10, 15, 20, 30, 40 mg / L, shaking for 20 min). HCOF was then collected and the supernatant was analyzed by HPLC-MS / MS or HPLC. The adsorption equilibrium of the covalent organic framework was determined by the same method (AFTs concentration was 2, 4, 6, 8 and 10 mg / L, shaking for 50 min; AGEs concentration was: 2, 5, 10, 15 and 20 mg / L, shaking for 30 min).

[0045] The results are as follows Figure 4-5 As shown, the prepared porous network adsorption material has high efficiency in adsorption performance for the target object.

[0046] Example 4: HCOF Repeatability Evaluation

[0047] 5.0 mg HCOF obtained in Example 1 was eluted with 5 mL of acetonitrile. Ultrasonication was performed for 20 min until no adsorption target was detected in the supernatant. The thoroughly cleaned material was placed in a vacuum oven and dried overnight at 40°C. The dried material was subjected to the same adsorption-elution-analysis steps as before, and the average value was determined three times in parallel. AFB1, AFB2, AFG1, AFG2, CML and CEL were selected as detection targets, and the results were repeated 10 times. The recovery rate of the target each time was compared. Figure 6 As shown, the hollow porous adsorption material has good reusability and is suitable for the application of actual samples.

[0048] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a hollow porous adsorption material, characterized in that: A covalent organic framework was successfully grown on the surface of the metal organic framework through an in situ growth method to form a core-shell structure composite material, and then the metal organic framework was etched by acid to prepare a hollow porous adsorption material.

2. The method for preparing the hollow porous adsorption material according to claim 1, characterized in that: The specific steps are as follows: Step 1: Dissolve Zn(NO3)2·6H2O and dimethylimidazole in 25 mL of methanol at a ratio of 1:

4. The resulting methanol solution of Zn(NO3)2 is marked as solution A, and the methanol solution of dimethylimidazole is marked as solution B. Add solution B to solution A and stir to react. Collect and dry the generated solid to obtain ZIF-8. Step 2: Disperse and dissolve 0.08 mM 1,3,5-tri(4-aminophenyl)benzene and 0.12 mM terephthalaldehyde in 25 mL methanol, add 8 mg ZIF-8, and then add lead chloride solution, mix thoroughly; after standing at room temperature, collect and dry the solid matter to obtain ZIF-8@COF; Step 3: Add 20 mg ZIF-8@COF to 10 mL 1M HAc for etching. Collect and dry the obtained solid material to obtain the hollow porous adsorption material HCOF.

3. The method for preparing the hollow porous adsorption material according to claim 2, characterized in that: In step 1, the molar ratio of Zn(NO3)2·6H2O to dimethylimidazole is 1:

4.

4. The method for preparing a hollow porous adsorption material according to claim 2, characterized in that: In step 2, 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde are dispersed and dissolved in methanol and ultrasonically treated until they are completely dissolved; after adding ZIF-8 and lead chloride solution, they are vigorously shaken for 10 seconds and then left to stand at room temperature for 24 hours.

5. The method for preparing the hollow porous adsorption material according to claim 4, characterized in that: The concentration of lead chloride solution is 0.1 mol / L.

6. The method for preparing a hollow porous adsorption material according to claim 2, characterized in that: The acetic acid concentration in step 3 is 1M.

7. The hollow porous adsorbent material prepared by the method for preparing the hollow porous adsorbent material according to any one of claims 1 to 6.

8. Use of the hollow porous adsorption material according to claim 7 in enriching pollutants in food.

9. The use according to claim 8, characterized in that: The hollow porous adsorption material is placed in the target solution, and the food contaminants are enriched by oscillating adsorption.

10. The use according to claim 9, characterized in that: The hollow porous adsorption material after enrichment of pollutants can be used to remove pollutants by eluting with acetonitrile and then reused to enrich food pollutants.